Women’s Work-Life Balance During Pandemic Covid 19 - Grace Amin; Filda Rahmiati; Dhiyaa Alyaa Chani Wudd (UNIVERSITAS PAKUAN, 2023)
Pandemic Covid 19 changes many aspects of life. Many employees have to work from home (WFH) to reduce the spread of Covid19. This research is aimed to analyze the influence of remote working, work stress, work-family conflict, and workload on womens work-life balance. This study took quantitative data by using the SEMPLS method with 275 respondents. From this research, we found that all variables are having a direct and indirect effect on Work-Life Balance. All companies must maintain the work-life balance of women employees